DEVELOPMENT OF ELECTRONIC GOVERNANCE BASED REGIONAL GOVERNMENT MANAGEMENT - Charliyan, Anton (Jurnal Multidisiplin Sahombu, 2023)
Government management is a process of carrying out governance activities or government management by authorities or government administrators in order to achieve the stated goals, namely increasing people's welfare. To support the success of the service and improve the quality of the service, it is necessary to have a service management procedure known as government management. Basically government management (public management) is the main factor in a public administration to achieve predetermined objectives with existing facilities and infrastructure, including the organization and available sources of funds and resources, as well as in this case the local government. Local governments are currently required to carry out reforms in various sectors, this is due to the increasing needs of the people who are increasingly complex day by day. Changes in management in the government sector are a necessity that really need to be improved as much as possible so that this process can later be felt by all circles of society at large. Right in 2003, the government officially issued Presidential Instruction No. 3 of 2003 as a follow-up effort to support the implementation of e-government in order to improve the quality of service to the public, especially in terms of providing information and supporting the principles of good governance. In summary, E-government as a service concept that uses information technology can be divided into several levels, namely first, preparation, second, maturation, third, consolidation; and fourth utilization. The application of the e-governance system is expected to be able to upgrade the government system in a direction that is more efficient, effective, transparent and accountable.